Kuantan Clay Properties and Examination of Fly Ash and Bottom Ash Utilization as Soil Stabilizer - Achmad Fauzi, Abdul Wahab; Wan Mohd Nazmi, Wan Abdul Rahman; Usama Juniansyah, Fauzi (Penerbit UMP, 2011)
This publication presents the engineering properties of Kuantan clay and proposes an assessment of the utilization of fly ash and bottom ash as stabilizer of soft sugbrades material in highway construction. The research conducts various contents of fly ash and bottom ash to different types of clay soils from various sites in Kuantan. The compaction tests and California Bearing Ratio (CBR) tests were applied in soil samples to estimate the optimum mixture design. The samples were set up by mixing soil samples with various contents of fly ash and bottom ash at optimum water content. The accomplishment of subgrade stabilization depends on the engineering properties of soils and characteristic of fly ash and bottom ash. The laboratory result shows that the strength gain in stabilization mainly depends on two factors: fly ash and bottom ash content and molding water content. The variation content of fly ash and bottom ash were 4%, 8% and 12% by total weight.